Construcción de las ecuaciones en la ciencia física - Holguín Tabares, Carlos Arturo (Revista Científica, 2011)
How are the physics equations gotten? there is not an only simple answer, because to construct the algebraic equations with the composition rules in experimental quantities associate; when one of them change in function of the other during an experiment, requires a conscious and logical process, since this to define the concept of experimental variables and the other more magnitudes present in physics phenomenons, it gives us possibilities to study different duly argue process. some of these methods that connect the variables are: graph analysis with different papers, use of the conservation rules, regression analysis and other to construct algebraic equations.